ISU-ISU KRITIS DALAM PENDIDIKAN ISLAM - Sukari; Ahmad Akbar Al Faizi; Anisa Nurkhotimah (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Islamic education plays a strategic role in shaping the character, morals, and competencies of students, enabling them to face the challenges of the times. However, in its development, Islamic education faces various critical issues that affect its quality and relevance. This study aims to examine and analyze critical issues in Islamic education, including the curriculum, the quality of teaching resources, learning methods, the integration of religious and general knowledge, and the challenges of globalization and technological development. The research method used is library research, which examines various sources of literature, including books, scientific journals, and relevant educational policy documents. The results indicate that Islamic education still faces problems such as disparities in the quality of educational institutions, weak learning innovation, and the suboptimal internalization of Islamic values ​​in the educational process. Therefore, efforts are needed to reform and strengthen the Islamic education system through the development of an adaptive curriculum, increasing the professionalism of educators, and the wise use of technology to ensure Islamic education remains relevant and able to meet the challenges of the modern era.